Premature Rupture of Membranes and Severe Weather Systems - Wheeler, Mackenzie L.; Oyen, Michelle L. (Frontiers in Physiology, 2020)
There has long been anecdotal evidence of early labor and delivery in severe weather events leading to preterm birth. In particular, significant barometric pressure changes are associated with hurricanes and bomb cyclones. Some authors have related these low pressure weather events to premature rupture of membranes, hypothesizing that the membranes act as an inflated balloon and respond directly to pressure changes. In this article, the key literature including data supporting this hypothesis is reviewed. A simple numerical model, based on a competition between the driving and resisting forces for membrane failure, is presented. This model provides a quantitative mechanism for membrane rupture in the context of storms with low atmospheric pressure. Other sequelae of severe storms that are unrelated to membrane rupture are also discussed. Labor and delivery in the context of major weather events should be understood in a holistic framework that includes both exogenous and endogenous factors relevant to the pregnant patient.